2010
DOI: 10.1007/s11368-010-0306-3
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene effects on methanotroph community and methane oxidation rate, tested by dose–response experiment and resistance and resilience experiment

Abstract: Purpose Methanotrophs are an important group of bacteria that can metabolize methane. Polycyclic aromatic hydrocarbons (PAHs) are widespread contaminants and present in all ecosystems. We hypothesize that PAHs may affect methanotrophs and methane oxidation. In this study, we assessed dose-response curves for the inhibition of methane oxidation and methanotrophs diversity by pyrene, and resistance and resilience of soil methane oxidation rate and methanotrophs composition in response to pyrene contamination. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…This was consistent with there being functional redundancy between the species, but with the caveat that apparently unimportant species in a stable environment might have a role in maintaining function in a fluctuating environment, that is, be important for stability (Bell et al, 2005). At high concentrations, diversity was decreased and no recovery was observed (Deng et al, 2011). Changes in species richness are most often considered when investigating the role of biodiversity for eco-system functioning while biodiversity encompasses other components such as evenness (the relative abundance of species).…”
Section: Insights Into the Underlying Mechanismssupporting
confidence: 74%
“…This was consistent with there being functional redundancy between the species, but with the caveat that apparently unimportant species in a stable environment might have a role in maintaining function in a fluctuating environment, that is, be important for stability (Bell et al, 2005). At high concentrations, diversity was decreased and no recovery was observed (Deng et al, 2011). Changes in species richness are most often considered when investigating the role of biodiversity for eco-system functioning while biodiversity encompasses other components such as evenness (the relative abundance of species).…”
Section: Insights Into the Underlying Mechanismssupporting
confidence: 74%
“…The hypothesis was tested previously with in situ data from marine sediment, where depth was used as a proxy for disturbance (Boer et al, 2009), but only a weak relationship was observed. A number of studies have been conducted on soil microorganisms, in which no relationship (Fierer et al, 2003; Wakelin et al, 2010; Deng et al, 2011) or only a negative impact of disturbance has been reported (Kim et al, 2013). Here, the positive relationship was observed both at the beginning of the experiment, when the nutrient load was high, and later, when the organic carbohydrate concentrations were significantly lower.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that gene expression Fig. 1 The acute lethal response of E. fetida exposed to AHTN (a) and HHCB (b) after 7-day and 14-day exposures in natural soil toxicity test Table 3 The growth rate and reproduction rate (cocoon/worm) of E. fetida after a 28-day exposure to the solvent control and AHTN or HHCB-spiked natural soil can serve as early-response biomarker for chemical exposure, because they can be detected at low concentrations of chemicals and before morphological or reproductive effects become visible (Ryan et al 2005;Deng et al 2011). Therefore, there is a great need to develop gene expression analysis for improving traditional toxicological tests (Zhou et al 2004).…”
Section: Gene Expression Response Of Antioxidant Enzymesmentioning
confidence: 99%